2014
DOI: 10.3109/01942638.2014.957428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cognitive Intervention on Children with ADHD

Abstract: Although not considered a diagnostic criterion in DSM-IV, motor difficulties in children with Attention Deficit Hyperactivity Disorder (ADHD) are commonly reported. Prevalence of co-morbidity of ADHD and Developmental Coordination Disorder is as high as 50%. Cognitive Orientation to daily Occupational Performance (CO-OP) is a problem-solving approach originally developed for children with Developmental Coordination Disorder. In this approach, therapists support children to use cognitive strategies in a process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 26 publications
6
36
0
Order By: Relevance
“…The above-mentioned results are consistent with previous studies providing evidence for the effectiveness of CO-OP as an intervention to improve motor performance in children with DCD (Miller et al, 2001;Ward & Rodger, 2004), ADHD (Gharebaghy, Rassafiani, & Cameron, 2015), and CP (Cameron et al, 2016). The results of this study provide evidence for the effective application of CO-OP for children with CP.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The above-mentioned results are consistent with previous studies providing evidence for the effectiveness of CO-OP as an intervention to improve motor performance in children with DCD (Miller et al, 2001;Ward & Rodger, 2004), ADHD (Gharebaghy, Rassafiani, & Cameron, 2015), and CP (Cameron et al, 2016). The results of this study provide evidence for the effective application of CO-OP for children with CP.…”
Section: Discussionsupporting
confidence: 91%
“…Considering the improvement of motor difficulties through the adoption of the CO-OP approach for children with CP, the results can be deemed promising. The results of this study are consistent with the study by Polatajko et al, (2001), which showed improvement in performance of motor test components through CO-OP intervention, and with the study by Gharebaghy et al (2015), which showed improvement of motor performance in the BOTMP in children with ADHD (Gharebaghy, et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Evidence of eight intervention approaches implemented among children or adolescents was reported in the reviewed publications. The Cognitive Orientation to daily Occupational Performance (CO‐OP; Polatajko & Mandich, ) was the most common intervention reported and was implemented in seven articles (Banks, Rodger & Polatajko, ; Gharebaghy, Rassafiani & Cameron, ; Missiuna et al ., ; Phelan, Steinke & Mandich, ; Rodger & Brandenburg, ; Rodger & Liu, ; Rodger, Pham & Mitchell, ). The remaining interventions are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…It was originally designed for children with developmental co-ordination disorder, and for that group, there is strong evidence of effectiveness in goal achievement [24][25][26]. There is also evidence for CO-OP in adults with neurological disability after stroke [27][28][29] or traumatic brain injury [30] as well as in children with neurodevelopmental disabilities, such as attention deficit hyperactive disorder [31] and, recently, in children with CP [5,32]. However, we have found no studies evaluating the use of CO-OP in adults with CP or in persons with SB, and nor has CO-OP, to the best of our knowledge, been used or tested in a Swedish context.…”
Section: Introductionmentioning
confidence: 99%